Rethinking the EU Financial Architecture - Lourdes Acedo Montoya (Intereconomics, 2023)
The European Union has weathered a number of turbulent storms in recent years from the COVID-19 pandemic to the ongoing war in Ukraine. These crises have highlighted the limitations of the EU budget and the need for the flexibility to adequately respond to challenges in real time. They have also raised questions about the legal feasibility of more common debt following a dramatic increase in EU borrowing. What are the obstacles - and the opportunities - for the EU's public finances in the face of the numerous crises of our time? Is it possible to balance predictability for long-term investments and flexibility to react to unexpected turns of events? This Forum addresses these questions and builds on the discussions at the 2023 joint Intereconomics/CEPS conference.
Keywords: H41; H60; E62; E61; 330; EU budget; EU-Haushalt